Pendampingan Pencatatan Keuangan Sederhana untuk UMKM di Desa Banyu Urip - Siti Rahmah Ayu; Trisninawati Trisninawati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This mentoring activity for simple financial record-keeping was motivated by the low level of financial literacy and recording habits among MSME actors in Banyu Urip Village, which potentially hinders the sustainability and growth of their businesses. The objective of this Thematic Community Service Program (KKNT) was to enhance the understanding and practical skills of MSME actors in implementing simple bookkeeping. The methods employed included initial observation, coordination with village officials, interviews, and direct mentoring through training and practical sessions on filling out daily cash books. The results of the activity indicated positive improvements in the understanding of basic financial recording concepts, practical skills in recording transactions, and awareness of the importance of separating business and personal finances. MSME actors became more motivated to apply regular record-keeping, which is expected to enhance transparency, cash flow management, and future business planning.